Sensitivity Analysis and Optimization of Facade Design to Improve Daylight Performance of Tropical Classrooms with an Adjacent Building - Atthaillah; Rizki A. Mangkuto; Andik Bintoro (Journal of Daylighting)
This study examines the daylighting performance of a classroom with bilateral opening typology and an adjacent building on one side. The openings are located on the east and west sides of the classroom, with the adjacent building situated on the west side. The case selection is based on the observation that many Indonesian urban classrooms are often blocked from daylight by the adjacent building. Accordingly, this study examines the optimal design for annual visual comfort and daylighting performance criteria for such cases, which are prevalent in the tropical regions of Indonesia. To achieve this, computational simulation was conducted. The model was constructed using Ladybug Tools, while the annual visual comfort and daylight simulation was performed simultaneously using Radiance under Grasshopper. Sensitivity analysis was conducted to identify the most significant façade design variables, including external horizontal shading depth, shading elevation, window-to-wall ratio (WWR), and distance to the adjacent building on a bilateral opening typology classroom. The most optimal design was obtained from multilinear regression prediction model based on 5,731 simulation samples. The three most influential design variables on the annual visual comfort and direct sunlight are the horizontal shading depth, shading elevation, and WWR on the east facade. The optimal design solution for the horizontal shading depth, shading elevation, and window-to-wall ratio (WWR) on the east and west façades have similar values of 2.6 m, 2.7 m, and 10%, respectively. The distance to adjacent buildings is recommended to be maintained at 0.5 m from the edge of the external shading on the west side.